2017
DOI: 10.22159/ajpcr.2017.v10i11.20801
|View full text |Cite
|
Sign up to set email alerts
|

New Insights of Mammary Gland During Different Stages of Development

Abstract: Mammary gland is a unique organ with its function of milk synthesis, secretion, and involution to prepare the gland for subsequent lactation. The mammary epithelial cells proliferate, differentiate, undergo apoptosis, and tissue remodeling following a cyclic pathway in lactation -involutionlactation cycle, thus fine tuning the molecular events through hormones, and regulatory molecules. Several studies are performed on the mammary gland development, lactogenesis, and involution process in molecular details. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…The other genes identified on BTA14 (SHARPIN, CYC1, EXOSC4, PARP10, OPLAH, GRINA, and PLEC) were recently strongly associated with milk production traits, including PROT [37,93,102]. According to Jena et al [103], SHARPIN influences mammary gland development and controls extracellular matrix organization of stroma during branching morphogenesis, which induces alveologenesis during pregnancy and lactation. Moreover, Lin et al [104] found strong association of SHARPIN, CYC1, EXOSC4, and PARP10 with milk serum albumin, which is one of the main protein contents of cattle milk.…”
Section: Candidate Genes For Protein Yieldmentioning
confidence: 99%
“…The other genes identified on BTA14 (SHARPIN, CYC1, EXOSC4, PARP10, OPLAH, GRINA, and PLEC) were recently strongly associated with milk production traits, including PROT [37,93,102]. According to Jena et al [103], SHARPIN influences mammary gland development and controls extracellular matrix organization of stroma during branching morphogenesis, which induces alveologenesis during pregnancy and lactation. Moreover, Lin et al [104] found strong association of SHARPIN, CYC1, EXOSC4, and PARP10 with milk serum albumin, which is one of the main protein contents of cattle milk.…”
Section: Candidate Genes For Protein Yieldmentioning
confidence: 99%
“…It should be noted that this invagination process is not dependent on hormonal action [65]. At the onset of puberty, ovarian steroid hormones accelerate the extension and branching of the mammary ducts [66]. During pregnancy, ductal branching continues.…”
Section: Internal Structurementioning
confidence: 98%
“…By and large, the mammary gland develops mainly postnatally in puberty, pregnancy, lactation, and involution—stages in which reproductive hormones and growth factors play a decisive role [ 3 , 4 , 5 ]. At the onset of puberty, the ovarian steroid hormones regulate branching morphogenesis by promoting the extension and branching of mammary ducts ( Figure 1 C) [ 5 ]. Then, at a later stage, the epithelium infiltrates the fat-pad stroma and builds the mammary gland.…”
Section: Mammary Gland Structure and Developmentmentioning
confidence: 99%
“…It has a complex structure comprising a branching epithelium surrounded by a stromal microenvironment [ 1 ]. The interaction between these two compartments, together with a series of growth hormones and growth factors, modulates its development [ 2 , 3 , 4 , 5 ]. Notably, in breast cancer (BC), alterations in the signaling pathways regulating the development of the physiological mammary gland contribute to cancer growth [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%